INOVASI PEMERINTAH DESA LOBUK DALAM MEWUJUDKAN DESA MANDIRI DAN BERKELANJUTAN - Nur Alfiyah; Nur Inna Alfiyah (PUBLIC CORNER, 2022)
Policies to improve the living standards of people in rural areas it has been widely used in various programs. Various programs that have been implemented through existing policies so far show the impression that there has not been a significant pattern or formula that can continuously improve the standard of living of the people in the village, especially in the villages. So to break the chain of ineffectiveness of the policy, an innovation is needed so that the existing villages can be separated from the uncertainty of the realization of a policy. Innovations that exist at this time can be done by utilizing the sophistication of technology and information in the era of digitalization. One of them is by utilizing the internet as a means of innovation in an effort to develop villages towards independent and sustainable villages. As has been done by Lobuk Village, Bluto District, which is able to create innovation by providing services based on android applications, so the purpose of this research is to see how the innovations made by Lobuk village in realizing an independent village. This study uses a qualitative descriptive method to describe, explain and answer in more detail village problems. The results showed that Lobuk village in an effort to implement existing innovations was able to provide improved services to the community, this was proven by the release of Lobuk Village as the winner in the village and urban village competition as a champion at the East Java Province level as the only and first to become an independent village in Sumenep Regency. Keywords :Innovation, Independent and Sustainable Village, Lobuk Village